Technology readiness evaluation in dry choux pastry SMEs - Tarigan, Amenda Septiala (Jurnal Mantik, 2025)
This study evaluated the readiness level of technoware (equipment and machinery) and humanware (workforce competency) in a small-scale dry choux pastry enterprise to comply with the Indonesian National Standard (SNI) 2973:2011 for biscuits. The assessment was conducted using the Quality Function Deployment (QFD) framework and Analytical Hierarchy Process (AHP) to align customer needs and product quality standards with the production processes. Expert-based scoring was applied to measure the technological sophistication of production equipment and human capabilities based on UNESCAP classifications. The study identified the gap between actual conditions and the standard requirements by calculating aggregate scores for both technoware and humanware components across each production stage. The results revealed readiness gaps reaching 50.3% in microbial safety and 49.5% in free fatty acid (FFA) control, with technoware deficiencies most severe in packaging and filling, while humanware gaps were prominent in ingredient preparation and cooking. Improvement priorities were proposed using planning and technical matrices to calculate improvement ratios and normalized weights. Key improvement targets included moisture content control (improvement ratio = 1.28), flavor consistency, and heavy-metal safety. To assist micro and small bakery enterprises, this research suggests that incremental investments be made in PID-controlled ovens, stainless steel trays, and structured operator training in GMP and sensory evaluation. The main objective of this study is to develop a diagnostic framework that guides SME owners in prioritizing technology and competency upgrades to achieve sustainable compliance with SNI 2973:2011. The study concludes that a strategic focus on upgrading both machinery and human skillsets is essential for small food enterprises aiming to meet national food safety and quality standards